1996
DOI: 10.1007/bf02354473
|View full text |Cite
|
Sign up to set email alerts
|

Mail vs. telephone surveys of criminal justice attitudes: A comparative analysis

Abstract: This study compares results from surveys using two modes of administration. A subset of questions from the 1992 Texas Crime Poll, a statewide poll conducted annually by mail, was replicated in telephone interviews using the Computer Assisted Telephone Interviewing System. The phone survey yielded better participation rates but less complete responses to individual attitude questions than did the mail poll. As expected, the mail survey was less expensive but less efficient than the automated phone survey. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The jury pools in Florida consist of a random selection of residents 18 years of age and older who possess a valid state driver's license or state identification card. Despite any shortcomings related to statutory exclusions for those under eighteen years of age, protected populations, or law enforcement personnel, the jury pool offers social scientists a cost-effective, convenient, accessible, and fairly representative sample of the local community (Farnworth, Bennett, & West, 1996). According to 1990 Census data, this jury pool sample of participants in this study closely resembles the demographic characteristics of Hillsborough County with two exceptions: potential jurors had a slightly higher household income and were better educated.…”
Section: Methodsmentioning
confidence: 95%
“…The jury pools in Florida consist of a random selection of residents 18 years of age and older who possess a valid state driver's license or state identification card. Despite any shortcomings related to statutory exclusions for those under eighteen years of age, protected populations, or law enforcement personnel, the jury pool offers social scientists a cost-effective, convenient, accessible, and fairly representative sample of the local community (Farnworth, Bennett, & West, 1996). According to 1990 Census data, this jury pool sample of participants in this study closely resembles the demographic characteristics of Hillsborough County with two exceptions: potential jurors had a slightly higher household income and were better educated.…”
Section: Methodsmentioning
confidence: 95%
“…Their study found that personal interview surveys are more susceptible to this Downloaded by [Temple University Libraries] at 00:20 05 June 2016 kind of bias than are self-administered surveys. Researchers who have compared responses to interviewer-administered surveys (phone or face to face) and self-administered surveys (mailed or dropped off) in probability samples drawn from the same sampling frame and administered in the same time frame have reported significant differences by mode in reports of drug use and illegal activity (Aquilino & LoSciuto, 1990); personal health status and chronic conditions (McHorney, Kosinski, & Ware, 1994;Siemiatycki, Campbell, Richardson, & Aubert, 1984); quality of life, crime, and safety (Krysan, Schuman, Scott, & Beatty, 1994); and punishment of criminals (Farnworth, Bennett, & West, 1996). These studies have concluded that respondents are more forthright in exposing sensitive information or attitudes in self-administered surveys.…”
Section: Nonresponse and Response Biasmentioning
confidence: 98%
“…3 The use of telephone interviews and open-ended questioning do present some difficulties. Research suggests that respondents may be less likely to fully disclose negative attitudes toward the police when talking to interviewers (see Farnworth, Bennett, & West, 1996;Hennigan, Maxson, Sloane, & Ranney, 2002;Krysan, Schuman, Scott, & Beatty, 1994;McHorney, Kosinski, & Ware, 1994). Telephone or in-person interviews may result in fewer reports of negative attitudes toward the police, especially when contrasted with mail-in surveys.…”
mentioning
confidence: 99%